2016
DOI: 10.1002/ece3.2416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different root endophytic fungi on plant community structure in experimental microcosms

Abstract: Understanding the effects of root‐associated microbes in explaining plant community patterns represents a challenge in community ecology. Although typically overlooked, several lines of evidence point out that nonmycorrhizal, root endophytic fungi in the Ascomycota may have the potential to drive changes in plant community ecology given their ubiquitous presence, wide host ranges, and plant species‐specific fitness effects. Thus, we experimentally manipulated the presence of root endophytic fungal species in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…The many impacts of fungal endophytes on their hosts make these microbes critical in structuring plant communities and the terrestrial ecosystems they sustain (Rudgers et al, 2004;Afkhami & Strauss, 2016;Aguilar-Trigueros & Rillig, 2016). The study of plants as holobionts composed of host and complex microbiome is still in the early stages (Vandenkoornhuyse et al, 2015) and many studies only investigate the effects of a few individual fungi on their hosts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The many impacts of fungal endophytes on their hosts make these microbes critical in structuring plant communities and the terrestrial ecosystems they sustain (Rudgers et al, 2004;Afkhami & Strauss, 2016;Aguilar-Trigueros & Rillig, 2016). The study of plants as holobionts composed of host and complex microbiome is still in the early stages (Vandenkoornhuyse et al, 2015) and many studies only investigate the effects of a few individual fungi on their hosts.…”
Section: Introductionmentioning
confidence: 99%
“…The study of plants as holobionts composed of host and complex microbiome is still in the early stages (Vandenkoornhuyse et al, 2015) and many studies only investigate the effects of a few individual fungi on their hosts. Experiments that have tested the effects of many strains or combinations of multiple fungi have revealed that endophyte effects can differ between closely related fungi and that interactions between microbiome members matter for plant host outcomes (Violi et al, 2007;Mandyam et al, 2012Mandyam et al, , 2013Reininger et al, 2012;Aguilar-Trigueros & Rillig, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, since plant roots are consistently exposed to and colonized by diverse fungal species (Wearn et al. ), it will be critical that future studies investigate whether different combinations of endophytic and mycorrhizal fungi interact synergistically or antagonistically in plant tissues and how their overall effects on plant defense change with environmental conditions (Partida‐Martínez and Heil , Aguilar‐Trigueros and Rillig ).…”
Section: Discussionmentioning
confidence: 99%
“…While the root endophytic fungus P. indica has attracted increasing attention for its potential to enhance growth and performance of a wide range of crop plants (Weiß et al. ), the ecological significance of other endophyte species remains poorly characterized (Aguilar‐Trigueros and Rillig ).…”
Section: Introductionmentioning
confidence: 99%
“…Plants are host to a wide variety of microbes that do not appear to cause obvious disease, and there is growing realization that many of these endophytes can have cryptic effects on plant growth, physiology, and fitness (Rodriguez et al., ; Aguilar‐Trigueros and Rillig, ). Microbes are considered to be pathogens if they cause obvious disease symptoms, and generally these symptoms become evident after the pathogen has successfully established itself within the host.…”
mentioning
confidence: 99%